Role regulation and normative expectations: the discursive erasure of Middle Eastern forced migrants in U.S. news outlets. Issue 6 (2nd November 2019) - Partain, Laura P. B.
ABSTRACT: This thematic analysis of 510 news articles – spanning the leftist-rightist ideological spectrum – examines media rhetoric surrounding President Trump's 27 January 2017 Executive Order (EO) 13769 barring immigrants and refugees from U.S. resettlement. In this article, I examine how both liberal and conservative news media rhetoric reinforce respectability politics that create a hierarchy of victimhood for those affected by the EO. Interrogating U.S. civil society's discursive construction of the forced migrant, I expose expectations for appropriate roles for these communities seeking asylum, though these roles are often veiled by normative U.S. mythology. As this analysis illustrates, the news media articles' discursive erasure of Syrian, Iranian, Sudanese, Iraqi, Libyan, Somali, and Yemeni immigrants and refugees elide forced migrant self-representation and neglect the political/historical reasons for fleeing from their nations of origin.